Immunometabolism: new insights and lessons from antigen-directed cellular immune responses - Ramalho, Renata; Rao, Martin; Zhang, Chao; Agrati, Chiara; Ippolito, Giuseppe; Wang, Fu-Sheng; Zumla, Alimuddin; Maeurer, Markus (Seminars in immunopathology, 2020)
Modulation of immune responses by nutrients is an important area of study in cellular biology and clinical sciences in the context of cancer therapies and anti-pathogen-directed immune responses in health and disease. We review metabolic pathways that influence immune cell function and cellular persistence in chronic infections. We also highlight the role of nutrients in altering the tissue microenvironment with lessons from the tumor microenvironment that shapes the quality and quantity of cellular immune responses. Multiple layers of biological networks, including the nature of nutritional supplements, the genetic background, previous exposures, and gut microbiota status have impact on cellular performance and immune competence against molecularly defined targets. We discuss how immune metabolism determines the differentiation pathway of antigen-specific immune cells and how these insights can be explored to devise better strategies to strengthen anti-pathogen-directed immune responses, while curbing unwanted, non-productive inflammation.